The cicada genus Guyalna Boulard & Martinelli, 1996 (Hemiptera: Cicadidae: Cicadinae: Fidicinini): generic description, twelve new combinations, and a key to species - Sanborn, Allen F. (Zootaxa, 2016)
The cicada genus Guyalna Boulard and Martinelli, 1996 is described fully for the first time. Dorisiana bogotana (Distant, 1892), Dorisiana brisa (Walker, 1850), Fidicinoides coffea Sanborn, Moore & Young, 2008, Fidicinoides distanti (Goding, 1925), Fidicinoides flavipronotum Sanborn, 2007, Dorisiana glauca (Goding, 1925), Dorisiana panamensis (Davis, 1939), Fidicinoides variegata (Sanborn, 2005), and Dorisiana viridifemur (Walker, 1850) are transferred to the genus Guyalna to become Guyalna bogotana (Distant, 1892) n. comb., Guyalna brisa (Walker, 1850) n. comb., Guyalna coffea (Sanborn, Moore & Young, 2008) n. comb., Guyalna distanti (Goding, 1925) n. comb., Guyalna flavipronotum (Sanborn, 2007) n. comb., Guyalna glauca (Goding, 1925) n. comb., Guyalna panamensis (Davis, 1939) n. comb., Guyalna variegata (Sanborn, 2005) n. comb., and Guyalna viridifemur (Walker, 1850) n. comb., respectively. Fidicinoides cachla (Distant, 1899), Fidicinoides compostela (Davis, 1934), Fidicinoides guayabana Sanborn, Moore & Young, 2008, are transferred to Dorisiana Metcalf, 1952 to become Dorisiana cachla (Distant, 1899) n. comb., Dorisiana compostela (Davis, 1934) n. comb., and Dorisiana guayabana (Sanborn, Moore & Young, 2008) n. comb., respectively. The current 25 species of the genus are listed along with their synonymies and known distribution of each species. Finally, a key to the species of Guyalna is provided.